Microstructure and Mechanical Properties of Aluminum Alloy Matrix Composite Reinforced with Nano MgO Particles - Baghchesara, M.A.; Abdizadeh, H.; Baharvandi, H.R. (Asian Journal of Chemistry, 2010)
Discontinuously reinforced aluminum composites are being recognized as an important class of engineering materials that are making significant progress. The reasons for their success are related to their desirable properties including low density, high hardness, high compressive strength, wear resistance, etc. Casting and powder metallurgy are the two major fabrication methods of aluminum matrix composites, though powder metallurgy is more complicated than casting, but it yields to a better interface between reinforcement and matrix alloy, improving mechanical properties of Al-nano MgO composite. Pure atomized aluminum powder with an average particle size of 1 μm and MgO particulate with an average particle size between 60-80 nm were used. Composites containing 1.5, 2.5 and 5.0 % of volume fraction of MgO were prepared by powder metallurgy method. The specimens were pressurized by cold isostatic pressure machine. The consolidation temperatures were 575, 600 and 625 °C. After sintering and preparing the samples, mechanical properties were measured. The results of microstructure, compression and hardness tests showed that addition of MgO particulates to aluminum matrix composites improve the mechanical properties.